Improvement Of In Vitro Regeneration Of Brassica Oleracea Subsp. Italica Cv. Green Marvel Through Organogenesis - Ravanfar, Seyed Ali (2009)

(untitled)
Broccoli (Brassica oleracea subsp. italica) cv. Green Marvel is an important vegetable crop grown in Cameron Highlands, Malaysia. Being an F1 hybrid crop, selfing will result in segregation in the F2 generation. In Malaysia, the production of hybrid seeds of cv. Green Marvel cannot be carried out due to the absence of parental stock material for hybridization. Therefore, the development of in vitro regeneration system is necessary to produce uniform and true-to-type plants of the cultivar. Currently, in vitro regeneration of other broccoli cultivars have been carried out but none has been reported on the cultivar Green Marvel. This study was carried out with the main objective of establishing a protocol for plant regeneration of broccoli cv. Green Marvel through multiple shoot formation from hypocotyl, shoot tip and cotyledon explants, followed by rooting and acclimatisation. All experiments were conducted and arranged in a Randomised Complete Block Design (RCBD). In the experiment on multiple shoot formation from hypocotyl explants, the concentrations of 6-benzylaminopurine (BAP) alone or in combination with α-naphthaleneacetic acid (NAA) or indol-3-butyric acid (IBA) were assessed. In treatments containing only BAP, 3 mg/l of the plant growth regulator produced the highest percentage of explant with shoots (96.7%) and the highest mean number of shoots per explant (6.03). In treatments containing BAP and NAA, the highest percentage of explant with shoots (93.3%) occurred on 1 and 3 mg/l BAP while the highest mean number of shoots (6.0) was obtained on 5 mg/l BAP. In treatments containing BAP and IBA, BAP alone enhanced shoot multiplication. The highest percentage of hypocotyl explant with shoots (100%) and highest mean number of shoots produced per explant (6.33) occurred on 3 mg/l BAP. Therefore, 3 mg/l BAP was considered the most suitable for adventitious shoot formation from hypocotyl explants of broccoli cv. Green Marvel. In the experiment on shoot multiplication from shoot tip explants, the concentrations of BAP either alone or in combination with NAA or IBA were assessed. The result showed that BAP at 5 mg/l produced the most number of shoots than any combinations of BAP with NAA or IBA. In treatments containing BAP and NAA, the highest percentage of explants with shoots (100%) and the highest mean number of shoots per explant (3.76) were on 5 mg/l BAP. In treatments containing BAP and IBA,, the highest percentage of shoot tip explants with shoots (96.7%) and the highest mean number of shoots produced per explant (2.83) also occurred on 5 mg/l BAP. BAP at 5 mg/l BAP was therefore the optimum hormonal treatment for shoot proliferation from shoot tip explants of broccoli cv. Green Marvel. In the experiment on multiple shoot formation from cotyledon explant using different combinations of BAP and NAA, the highest percentage of explant producing shoots (53.3%) and the highest mean number of shoots produced per explant (0.43) occurred on treatment combination consisting of 3 mg/l BAP and 1 mg/l NAA. The treatment combination consisting of 3 mg/l BAP and 1 mg/l NAA is therefore the most suitable for high frequency of shoot regeneration from cotyledon explant of broccoli cv. Green Marvel. In the experiment on rooting of shoots using different concentrations of auxins, the highest percentage of shoots with roots (100%) and the highest mean number of roots produced per explant (6.5) occurred on 0.2 mg/l IBA, but did not differ significantly compared to MSO medium. Meanwhile the highest mean length of root (2.46 cm) was attained on hormone-free MS medium (MSO). Thus, MSO medium was considered the most suitable medium for rooting of broccoli cv. Green Marvel shoots. In the acclimatisation study, various types of potting mixture were assessed. The highest percentage of survival (83.3%) occurred on medium containing sand+ soil (1:1) while the maximum root length (4.37 cm) and the highest plant height (7.87 cm) were attained in potting medium containing peatmoss+ perlite+ vermiculite (3:1:1). The mixture of peatmoss+ perlite+ vermiculite (3:1:1) was therefore considered the most suitable potting medium for broccoli cv. Green Marvel. Plantlets were well rooted and ready for field transfer after four weeks of acclimatisation. The study on multiple shoot formation concluded that BAP alone at 3 and 5 mg/l were more effective in inducing shoot proliferation on the hypocotyl and shoot tip explants of broccoli cv. Green Marvel, respectively, while BAP in combination with NAA was required for effective shoot formation from the cotyledon explants. The study on rooting showed that MSO was most suitable for high percentage of root formation, mean number of roots produced per explant and root length attained. In the acclimatisation study, the most suitable potting mixture consisted of peatmoss+ perlite+ vermiculite.